Complex abdominopelvic reconstruction by combined tensor fascia latae and superficial circumflex iliac artery perforator flaps. Issue 1 (3rd December 2018) - Luca‐Pozner, V; Boissiere, F; Rodriguez, T; Karra, A; Herlin, C; Chaput, B
Abstract : Background: Extensive full thickness abdominopelvic defects pose a difficult challenge to surgeons. Autologous tissues are versatile and can provide a satisfying reconstructive option for this type of defects. The tensor fascia latae (TFL) and superficial circumflex iliac perforator (SCIP) flaps provide a large area of vascularized tissue and their use in reconstructive surgery is well‐known. In this report, the authors present the experience of using combined TFL and propeller SCIP flaps for covering large abdominal and pelvic defects. Methods: Four patients underwent reconstruction of soft‐tissue abdominopelvic defects by combined TFL and SCIP flaps. Three were men and one woman, aged from 52 to 76 years. The etiologies of the defects were tissue loss after tumor resection in 3 cases and necrotizing fasciitis in the fourth case. Defect dimensions ranged from 32 × 20 cm to 45 × 17 cm. An acoustic handheld Doppler was utilized to detect perforator vessels, then TFL and SCIP flaps were elevated at the same time by 2 surgical teams. Donor sites of the flaps were closed primary except for one TFL flap donor site. The latter one was treated with negative pressure therapy and finally with a split‐thick skin graft. Results: The size of the TFL flaps ranged from 25–38 × 10–14 cm. Concerning the SCIP flaps, the dimensions ranged from 18–32 × 12–18 cm. The average flap dimensions were 30.25 × 11.75 cm for the TFL and 26.75 × 14 cm for the SCIP. Two TFL flaps presented a necrosis of the distal tip. All the other flaps survived entirely. Complete healing was achieved in all patients. Patients were followed for an average of 4 months postoperatively (ranging between 2 and 8 months). Conclusions: Combined TFL and SCIP flaps may represent an alternative reconstructive procedure for large abdominopelvic defects in well‐selected cases.